BRAIN DEATH IN PREGNANCY: A SYSTEMATIC REVIEW - Dhillon, Robinder; Auliya, Ahsan; Azhari, Ririn (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Brain death is a rare event in pregnancy. A recent case series estimated the prevalence of pregnancy among brain dead patients at 2.5. The care of a brain-dead pregnant women focuses on optimizing maternal recovery, considering fetal health impacts, and interventions for maternal support, including medication, radiation exposure, and preterm labor risks. The aim: This study aims to investigate brain death in pregnancy. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 17 articles, whereas the results of our search on ScienceDirect brought up 11 articles. The results of the search conducted by title screening yielded a total 12 articles for PubMed and 6 articles for ScienceDirect. We compiled a total of 12 papers, 7 of which came from PubMed and 5 of which came from ScienceDirect. We excluded 2 review articles, 3 duplicate articles, 1 article having ineligible subject, and 1 discussion article. In the end, we included five research that met the criteria. Conclusion: In this review, 80 of neonates were born alive. Somatic support of the brain-dead pregnant woman was perfomed to maximize perinatal outcomes. And during gestation, obstetricians must closely monitored fetal development.